A IDENTIFICAÇÃO NUM CASO DE INIBIÇÃO INFANTIL E A FUNÇÃO DO TRAÇO UNÁRIO NA DIREÇÃO DO TRATAMENTO - Nunes de Lima, Felipe (LINKSCIENCEPLACE, 2026)
In the essay Inhibitions, Symptoms and Anxiety Freud highlights the inhibition as a kind of defense against axiety, emphasizing the alterations of the Ego in this process. Taking this reference, this paper approaches the theme of inhibition from a clinical case of a child, in the search to demonstrate the reasons which lead the patient to present such clinical conditions. We still aim to expose the possibilities of treatment that showed up during the period in which the analysis took place, taking into consideration the particularities of child psychoanalysis. Based on Freud‟s and Lacan‟s studies, and through fragments of the case report, it was possible to point out the identification as a determinig mechanism of the alterations of the Ego. We also noticed that the patient‟s inhibition was a result of a pathological mourning, in which the identification played a fundamental role. Furthermore, we observed the importance of the unary trait in the patient‟s healing process, as it was through the recover the traits of the lost object that the patient was able to deal with the object a, thus reactivating the wish‟s movement.